Analisis Penerapan Model Pembelajaran Gerlach dan Ely dalam Pembelajaran Bahasa Indonesia di Sekolah Dasar: Analysis of the Application of Gerlach and Ely's Learning Model in Indonesian Language Learning in Elementary Schools - Balqis Oktaviani; Riris Nurkholidah Rambe (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
This study aims to analyze the application of the Gerlach and Ely Learning Model in Indonesian Language learning in Elementary Schools. This learning model is designed to improve teaching effectiveness by considering various factors that influence the learning process, such as student characteristics, learning objectives, and the physical and psychological conditions of the learning environment. This study uses a qualitative approach with a case study method conducted in several elementary schools in urban and rural areas. Data were collected through observation, interviews with teachers, and analysis of learning documents applied in the classroom. Then, I analyzed and tested the validity of the data to obtain perfect research results. The study results indicate that using the Gerlach and Ely model can improve students' understanding of Indonesian language learning materials, facilitate the communication process between teachers and students, and create a more interactive and enjoyable learning atmosphere. Its application has several challenges, such as limited learning media and teacher readiness in adapting this model. This study suggests that teachers should be trained more intensively on applying this learning model, and it is expected that it can be used as an alternative learning model in elementary schools. The application of the Gerlach and Ely Learning Model in Indonesian language learning in elementary schools shows a significant positive impact on the effectiveness and quality of learning. This model emphasizes systematic learning planning, actively involving students, and encouraging the use of supportive media to improve understanding of the material.